Corrosion protection of metals and alloys using graphene and biopolymer based nanocomposites - Amin, Hatem M.; Galal, Ahmed (Boca Raton : CRC Press, 2019)
With contributions from experts from both academia and industry, this book provides up-to-date reviews and promising approaches for corrosion control of metals and alloys via sustainable biopolymers and carbon nanomaterials coatings, focusing on the wonder material graphene which is more solid than steel. This book delivers essential information for improving the environmental and economic viability of current coating technologies. It is also a valuable reference for those who are interested in corrosion science and corrosion protection including professionals from the industry as well as academia.
CORROSION PROTECTION BY NATURAL/BIOPOLYMER COATINGS Corrosion: Introduction Anjali Peter and Sanjay K. Sharma Biopolymer Composites and Nanocomposites for Corrosion Protection of Industrial Metal Substrates Saviour A. Umoren and Moses M. Solomon Development of Green Vapor Phase Corrosion Inhibitors Victoriya Vorobyova, Olena Chygyrynets and Margarita Skiba Plant-Based Green Corrosion Inhibition: Need and Applications Anjali Peter and Sanjay K. Sharma Corrosion Protection Using Organic and Natural Polymeric Inhibitors Ebru S. Güler CORROSION PROTECTION USING GRAPHENE AND OTHER SMART COATINGS Carbon Nanoallotropes-Based Anticorrosive Coatings: Recent Advances and Future Perspectives Khaled M. Amin and Hatem M.A. Amin Analytical Techniques for Corrosion-Related Characterization of Graphene and Graphene-Based Nanocomposites Coatings Saman Hosseinpour, Ali Davoodi, Arash Sedighi and Faeze Tofighi Metal-Graphene Nanocomposites with Improved Mechanical and Anti-Corrosion Properties Liana Maria Muresan An Overview of the Effect of Graphene as a Metal Protector Against Microbiologically Influenced Corrosion (MIC) Reza Javaherdashti and Rahil Sarjahani Advanced Micro/Nanocapsules for Self-healing Smart Anticorrosion Coatings: A Review of Recent Developments Kayla Lee, Cynthia G. Cavazos, Jacob Rouse, Xin Wei, Mei Li and Suying Wei Plasma Electrolytic Oxidation: Anticorrosive and Biocompatible Coatings Aleksandra A. Gladkova, Dmitriy G. Tagabilev and Miki Hiroyuki
OCLC-licensed vendor bibliographic record.
Keywords: Corrosion and anti-corrosives.; Nanocomposites (Materials); SCIENCE / Chemistry / Industrial & Technical; SCIENCE / Life Sciences / General; TECHNOLOGY / Material Science